Dual effects of VEGF-B on activating cardiomyocytes and cardiac stem cells to protect the heart against short- and long-term ischemia–reperfusion injury. Issue 1 (December 2016) - Li, Guo-hua; Luo, Bin; Lv, Yan-xia; Zheng, Fei; Wang, Lu; Wei, Meng-xi; Li, Xian-yu; Zhang, Lei; Wang, Jia-ning; Chen, Shi-you; Tang, Jun-Ming; He, Xiaohua
Abstract Aims To investigate whether vascular endothelial growth factor B (VEGF-B) improves myocardial survival and cardiac stem cell (CSC) function in the ischemia–reperfusion (I/R) heart and promotes CSC mobilization and angiogenesis. Methods and results One hour after myocardial ischemia and infarction, rats were treated with recombinant human VEGF-B protein following 24 h or 7 days of myocardial reperfusion. Twenty-four hours after myocardial I/R, VEGF-B increased pAkt and Bcl-2 levels, reduced p-p38MAPK, LC3-II/I, beclin-1, CK, CK-MB and cTnt levels, triggered cardiomyocyte protection against I/R-induced autophagy and apoptosis, and contributed to the decrease of infarction size and the improvement of heart function during I/R. Simultaneously, an in vitro hypoxia-reoxygenation (H/R)-induced H9c2 cardiomyocyte injury model was used to mimic I/R injury model in vivo; in this model, VEGF-B decreased LDH release, blocked H/R-induced apoptosis by inhibiting cell autophagy, and these special effects could be abolished by the autophagy inducer, rapamycin. Mechanistically, VEGF-B markedly activated the Akt signaling pathway while slightly inhibiting p38MAPK, leading to the blockade of cell autophagy and thus protecting cardiomyocyte from H/R-induced activation of the intrinsic apoptotic pathway. Seven days after I/R, VEGF-B induced the expression of SDF-1α and HGF, resulting in the massive mobilization and homing of c-Kit positive cells, triggering further angiogenesis and vasculogenesis in the infracted heart and contributing to the improvement of I/R heart function. Conclusion VEGF-B could contribute to a favorable short- and long-term prognosis for I/R via the dual manipulation of cardiomyocytes and CSCs.